Characteristics of Instruments and Profile of Creative Thinking Ability of Students on Work and Energy Material - Annofi Sa'diyah Muflikhun; Woro Setyarsih (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2022)
Physics learning in secondary schools requires students to achieve learning objectives in developing conceptual skills and creative thinking by studying every problem that occurs in life using the concept of physics. However, the fact is that the physics material taught rarely relates the content of the lesson to everyday life, the lesson is mostly filled with convergent so that creative thinking skills cannot be measured. This study aims to apply the developed instrument and obtain empirical data on the validity of the instrument as well as a profile picture of students' creative thinking abilities. This study uses the ADDIE model with 5 stages, namely analysis, design, develop, implement, and evaluate. The test subjects in this study were 34 students of class X UMIPA 2 at MAN 1 Bojonegoro. The results of the development obtained 10 items of instruments that have been validated by 3 lecturers of physicists. Empirical validity was analyzed using Microsoft Excel software. Based on the data from the validity test results that have been analyzed, it shows that the instrument that has been developed is theoretically valid with an average V Aiken value in the material, construction and language domains, respectively 0.91; 0.91; and 0.87. The results of instrument validation are also declared empirically valid by having values: (a) Empirical validation of items with an rxy value range of 0.34 to 0.64; (b) The reliability of the instrument obtained an r11 value of 0.564 with a sufficient category, (c) The difficulty level of the instrument questions was 30% of the questions in the medium category and 70% of the questions in the easy category, (d) The discriminatory power of the instrument had 10% good questions, 40% enough questions, and 50% of the questions are not good. Creative thinking skills in students have a medium to very high category.